F127. Abnormal axonal inward rectification revealed in ALS patients with a low number of functionally intact motor units. (May 2018) - Larsen, Lotte H.; Jacobsen, Anna B.; Grafe, Peter; Fuglsang-Frederiksen, Anders; Tankisi, Hatice
Abstract : Introduction: Amyotrophic Lateral Sclerosis (ALS) is characterized by progressive loss of motor units. Changes in axonal excitability parameters have already been shown in earlier studies differing between severely and moderately affected disease by staging the disease using compound muscle action potential (CMAP) amplitude. However, CMAP amplitude may be normal until 50% of motor units are lost due to collateral sprouting. We aimed in this study to examine the axonal excitability properties in ALS patients correlated to disease severity determined by the novel motor unit number estimation (MUNE) method MScanFit MUNE (MScan). Methods: Twenty-five patients with ALS (mean age: 64.7 ± 3.2) were prospectively evaluated by multiple motor excitability measurements (strength duration time constant (SDTC), threshold electrotonus (TE), recovery cycle (RC), current–threshold relationship (I/V)) and MScan using Qtrac software in abductor pollicis brevis muscle. The patients were divided into two groups according to the number of motor units in MScan MUNE (MSFNUnits): (1) patients with MSFNUnits ⩾40 and (2) patients with MSFNUnits <40. The excitability parameters in patients were compared to 16 healthy controls aged 59.4 ± 2.9 using t-test. MSFNUnits were correlated to excitability parameters using linear regression analysis. Results: S2 accommodation decreased significantly in patients (20.67 ± 1.08) compared to healthy subjects (24.13 ± 0.838) (p = 0.03) whereas none of the other axonal excitability parameters differed between groups. S2 accommodation decreased in patients with MSFNUnits <40 (19.57 ± 1.64) while the minimum I/V slope increased (0.30 ± 0.02) compared to healthy controls (0.25 ± 0.01) (p < 0.02). ALS patients with MSFNUnits ⩾40 did not differ from healthy controls with regards to any of the excitability parameters. MSFNUnits correlated significantly to minimum I/V slope (r = −0.44) (p < 0.05). Conclusion: Axonal excitability parameters differ in different stages of ALS. Using MScan MUNE in staging of the disease severity may provide a more objective measure. The results in this study may suggest an increase in axonal inward rectification in ALS patients with low number of motor units. Further studies with larger patient groups are warranted.